Wpływ muzykoterapii receptywnej na ciśnienie tętnicze krwi podczas zabiegów masażu leczniczego u pacjentów po przebytym udarze mózgu = Impact of receptive music therapy on blood pressure during healing massage on patients after stroke - Tadych, Adam; Pospiech, Wojciech; Sielski, Łukasz (Journal of Education, Health and Sport, 2016)
Tadych Adam, Pospiech Wojciech, Sielski Łukasz. Wpływ muzykoterapii receptywnej na ciśnienie tętnicze krwi podczas zabiegów masażu leczniczego u pacjentów po przebytym udarze mózgu = Impact of receptive music therapy on blood pressure during healing massage on patients after stroke. Journal of Education, Health and Sport. 2016;6(10):263-278. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162076 http://ojs.ukw.edu.pl/index.php/johs/article/view/3933 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. Wpływ muzykoterapii receptywnej na ciśnienie tętnicze krwi podczas zabiegów masażu leczniczego u pacjentów po przebytym udarze mózgu Impact of receptive music therapy on blood pressure during healing massage on patients after stroke Adam Tadych2,4,Wojciech Pospiech1, Łukasz Sielski3,4 1. Katedra i Zakład Muzykoterapii, Collegium Medicum w Bydgoszczy, UMK w Toruniu 2. SKN „Muzykoterapii” przy Katedrze i Zakładzie Muzykoterapii, Collegium Medicum w Bydgoszczy, UMK w Toruniu 3. Klinika Medycyny Matczyno-Płodowej, Ginekologii i Neonatologii, Collegium Medicum w Bydgoszczy, UMK w Toruniu 4. Centrum Rehabilitacji, Wielospecjalistyczny Szpital Miejski im. dr E. Warmińskiego w Bydgoszczy Streszczenie Muzykoterapia ma swoje korzenie już w starożytności, odgłosy przyrody otaczające człowieka prowokowały go do naśladowania i przetwarzania ich dźwięku w różny sposób by tworzyć melodie przyjemne dla siebie. Ciągły postęp technologiczny daje nowe możliwości diagnozowania, a badaczom narzędzia do prowadzenia badań naukowych potwierdzających skuteczność muzykoterapii jako metody mieszczącej się w ramach współczesnej medycyny. Celem niniejszego opracowania jest określenie wpływu stymulacji muzyką pacjentów po przebytym udarze mózgu poddawanych zabiegom masażu leczniczego. Badaniem objęto 40 pacjentów (20 kobiet i 20 mężczyzn) po przebytym udarze mózgu (lewostronnym lub prawostronnym), przebywających na Oddziale Rehabilitacji. Średnia wieku wynosiła 71±7 lat. Pacjentów podzielono losowo na dwie równoliczne grupy, w każdej z nich było 20 osób. W obu grupach przez pięć kolejnych dni były wykonywane zabiegi rehabilitacyjne z zakresu masażu leczniczego. W grupie badanej dodatkowo chorzy byli poddawani muzykoterapii receptywnej utworami z repertuaru Kennego G, Katherine Jenkins oraz Andrea Bocelli’ego. W grupie kontrolnej wykonywano zabiegi masażu bez odtwarzania muzyki. Podczas każdego dnia badania wykonywano przed zabiegiem oraz po zabiegu pomiary ciśnienia tętniczego. Analiza zebranych wyników wskazuje na obniżenie wartości ciśnienia tętniczego krwi w grupie badanej w przeciwieństwie do wartości tych parametrów odnotowanych w grupie kontrolnej. Zebrane wyniki wskazują również za istotne statystycznie uzyskanie długotrwałego obniżenie wartości skurczowego ciśnienia krwi w grupie badanej. Niniejsze opracowanie wskazuje na istotne znaczenie muzykoterapii w profilaktyce wystąpienia wtórnego udaru mózgu, przez redukcję lub wyeliminowanie jednego z głównych czynników powstania choroby jakim jest nadciśnienie tętnicze. Słowa kluczowe: muzykoterapia, masaż leczniczy, udar mózgu, rehabilitacja, nadciśnienie tętnicze Summary Music therapy has its roots in the ancient times when the sounds of nature surrounding the man provoked him to imitate them and process in different ways to create a pleasant melodies. Continuous technological progress offers new opportunities to diagnose, and new tools for scientists to carry out research confirming the efficacy of music therapy as a method which is a part of modern medicine. The aim of this study is to define the effect of music stimulation in stroke patients, undergoing the therapeutic massage therapy. The study included 40 patients (20 women and 20 men) after a stroke ( left or right-sided), treated in the Department of Rehabilitation. The mean age of them was 71 ± 7 years. Patients were divided into two groups of 20 persons. In both groups, treatment including the therapeutic massage therapy was carried out for five days. In addition, the experimental group was subjected to a receptive music therapy with the works from the repertoire of Kenny G, Katherine Jenkins and Andrea Bocelli. In the control group treatment was carried out without playing music. Everyday during the study, both before and after the therapy, blood pressure rate of the patients were monitored. The analysis of the results indicates a decrease in blood pressure rate in the experimental group as opposed to the parameters observed in the control one. The results also indicate, as statistically important, the achievement of a long-term decrease in systolic blood pressure in the experimental group. The following study shows the importance of music therapy in the prevention of secondary stroke, by reducing or eliminating one of the main reasons of the disease, which is hypertension. Keywords: music therapy, therapeutic massage, stroke, rehabilitation, hypertension